(3ejRGf GdGYJOGd aj fbO GdQLGds - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s
(3ChdgG (B:s
(3jHOC GdehLhO efg CKfGA JQLeI YKeGf GdHQi Hbhdg (B: (3bGd eG YSi Cf Cbhd ajg , Cbhd (B: (3YSd ai LdO NfRjQ s
(3BNQgG (B:s
(3hGdOI Ce Mcje Yf Ce SdeI hYfgG HfJgG Je GdcJGH hGdMeO ddg Ydi fYeg hgPG eHdZ eG YfOi s
(3GdfSNI HgG MhGTs
(3HGdChQGb GdChdi JeRjbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B326 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B289s
(3JHUQGJ GdCUd (B:s
(3bQFJ Ydi GdeDda (B: (3bQGAJGf hGMOI SfI (B743 (3hGdKGfjI SfI (B745s
Keywords: (3GdJGQjNs